THE CIVILIZATIONAL ROLE OF MUSLIM FAMILY AWARENESS ON THE ADVOCACY OF HEALTH PROMOTION IN NORTHERN NIGERIA - Alkanchi, Hassan Malami; Binti MD Yusoff, Yusmini; Mohammad Zaidan, Ashraf; Umar Gokaru, Shuaibu; Umar, Sulaiman (Al-Iqro', 2024)
The increasing prevalence of chronic diseases and the rising lack of awareness about health promotion have sparked a renewed interest in promoting health promotion. The main objective of this study is to explore the civilizational role of the Muslim family on health promotion in northern Nigeria. This study employed a qualitative methodological approach using semi-structured interviews and focus group discussions. The participants were purposefully selected. In this study, a total of 15 participants were selected, which includes parents, Muslim healthcare workers, family counsellors, medical workers, and medical practitioners. The data was analysed using thematic analysis. Findings of the study revealed that Muslim families used strategies to foster health-promotion behaviours including health education awareness, family health counselling, health practices, religious teachings, and values that provide guidance. The findings further confirmed that healthy awareness creates an enabling environment in which healthy behaviours can be practiced, modelled, and encouraged. Finally, the findings unveiled that the social role of families has significant influence in promoting healthy behaviours, creating a healthy atmosphere that facilitates the prevention of disease, and health risks for effective human development. The study, therefore, recommended that health promotion initiatives should be designed, improved, and implemented by taking into consideration of the Islamic ethical values of health promotion to increase their usefulness for a healthy society for human development